Królewskie polowanie w eposach indyjskich - Grabowska, Barbara (Zoophilologica. Polish Journal of Animal Studies, 2018)
The article presents a study of the royal hunting practices of lunar and solar dynasties, using the great Sanskrit epics as literary sources. Both epics, the Mahabharata and the Ramayana, criticize the devastation and destruction of the forest area brought about by the hunting king and simultaneously praise the calming impact of forest hermitages on the environment. Ample provision was made for non-participation of hounds in hunting. The analysis showed that the deforestation and the tragic fate of indigenous hunting tribes continued to be the central problem of the texts. The king required the forest area for the purposes of agriculture and economy, brahmins set up hermitages here, but the forest used to be a tribal habitat first of all. The dominant Bharata tribe formed alliances by contracting marriages with more powerful hunting communities, while for the vulnerable ones there was no room left. Dehumanized, perceived as demonic or snake-like creatures and animals, they were doomed. The forests along the route of the expansion of the Bharata tribe were cut down or burnt, often together with their inhabitants: human tribes, animals and birds.